Welfare reform in California : early results from the impact analysis - Klerman, Jacob Alex (Rand, 2003)
Examines the effects of the California Work Opportunity and Responsibility to Kids (CalWORKs) program on work activity participation rates of welfare recipients, welfare caseloads, and outcomes for welfare leavers. While the CalWORKs reforms appear to have been responsible for some of the uniform improvement in outcomes shown by the analysis, the robust economy and other policy changes were probably also important.